A scientometric analysis of asthma research in Sri Lanka using Scopus and PubMed databases - Perera, K.K.N.L. (Library, University of Colombo, Sri Lanka, 2018)
Asthma is a disease characterized by recurrent attacks of breathlessness and wheezing, which vary in severity and frequency from person to person. In the digital age, scientometric analysis is used to track emerging developments in research areas which need special attention and funding. Objectives of this study were to analyse the publication rank, papers per 1000 population (PPTP), relative growth rate (R) and doubling time (Dt) of asthma research in Sri Lanka, using both Scopus and PubMed databases, during the period from 2000 to 2017. R is the increase in the number of publications per unit of time whereas Dt is the time required for the articles to double in number. Publication rank, PPTP, R and Dt are parameters frequently used in scientometric studies. According to Scopus, Sri Lanka is globally ranked 91st in asthma research. PPTP on asthma research in Sri Lanka is 0.0021, whereas India shows a value of 3.43. There is an inverse relationship between R and Dt. During 2000 -2006, R values of asthma research in Sri Lanka are lower than that of the world. However, during 2007-2017, asthma research in Sri Lanka shows higher R values compared to that of the world. When compared to Dt values of world during 2000 -2006, the Sri Lankan Dt values are higher. During 2007-2017, Sri Lankan Dt values are lower, compared to the world, indicating a potential for an advancement in the research area.
Keywords: asthma; doubling time (Dt); electronic information resources; publication rank; relative growth rate (R); Sri Lanka